Detection of traumatic intra abdominal injuries using MSCT in Hospital Tengku Ampuan Afzan, Kuantan: our preliminary experience - Hassan, Radhiana; Abd. Aziz, Azian; Mohd Yusof, Mubarak; Abdul Rashid, Mohd Amran; Sa'at@Mohd Yusof, Azlin; Che Mohamed, Siti Kamariah (2009)

(untitled)
.Blunt abdominal trauma may cause injury to various internal organs. • It is often difficult to accurately evaluate the site and extent of suspected internal injury clinically • Intra-abdominal injury may be masked by more obvious or compelling injuries elsewhere • The management of patients with solid organ injuries has changed dramatically, in most cases treatment has shifted from early surgical treatment to non-operative management • Hence, CT scan plays an important role in patient’s management as it provided a rapid, accurate assessment of abdominal viscera, retroperitoneum and abdominal wall